2000
DOI: 10.1093/pubmed/22.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the SF-36 health survey questionnaire with the Nottingham health profile in long-term survivors of a myocardial infarction

Abstract: At least in myocardial infarction survivors, the SF-36 appears a more sensitive tool and may have benefits for assessing health-related quality of life in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 26 publications
7
20
0
Order By: Relevance
“…As reported previously [11,12,14,[17][18][19], floor/ceiling effects in the SF-36 were found in very few subscales. When these effects did occur, they were not as pronounced as those for the NHP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As reported previously [11,12,14,[17][18][19], floor/ceiling effects in the SF-36 were found in very few subscales. When these effects did occur, they were not as pronounced as those for the NHP.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently this problem was referred to in many articles that used both instruments (in some of these publications the instruments were also compared with other instruments) in different patient groups: e. g., in the rehabilitation of patients with physical impairment [17], patients who had suffered accidents at work [18], patients who had suffered myocardial infarction [19], patients with venous ulcers [11], patients who had undergone heart surgery [14], patients with reduced growth hormones [12] and in general surveys [20]. The only study that explicitly found no difference in respect of floor effects between the two questionnaires [21] was marked by a very special characteristic: the random sample of the study comprised a normative population of elderly individuals (more than 65 years of age).…”
Section: Nhp and Sf-36mentioning
confidence: 99%
“…Comorbid heart disease or stroke was associated with relatively large deficits in ambulation, while comorbid arthritis or heart disease was associated with significant pain. While the type of heart disease was not specified in the NPHS, ischemic heart disease, angina, and congestive heart failure are all associated with pain [39][40][41]. The amount of pain reported in the diabetes and heart disease group far exceeded that associated with either condition alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, multiple dependent effect sizes were summarized according to the method proposed by Rosenthal and Rubin [23], which uses the intercorrelations between multiple dependent outcomes to compute a more precise estimate of a pooled effect size for multiple dependent variables. Intercorrelations for QoL instruments were derived from published literature [24,25,26,27,28,29,30,31,32]. If no such intercorrelations could be derived from the literature, the mean of the dependent effect sizes was computed.…”
Section: Methodsmentioning
confidence: 99%